Dampak Moderasi Fitur Rekomendasi Tiktokshop pada Kecepattanggapan Penjual dan Kepuasaan Pelanggan Terhadap Keputusan Pembelian Konsumen - Maha Martabar Mangatas Lumbanraja; Rahmat Junaidi; Sharnuke Asrilsyak (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
Changes in the use of Social Media, from behavior that connects between communities to a place for meeting the needs of parties as a form of virtual market, which is mediated and moderated by Social Media Marketing such as the Tiktop Shop. Tiktop Shop has changed from an application that provides digital content to a market for its users, involving recommendation features through an algorithm so that users can find what they need. This research was conducted on Tiktop Shop customers in Pekanbaru City, involving 165 respondents. Data collected through a research questionnaire and analyzed using the Partial Least Square approach. The results showed that the responsiveness of the seller is a factor that influences consumer purchasing decisions, while customer satisfaction is not an influencing factor. Meanwhile, the recommendation factor in this study strengthens the influence of causal variables on purchasing decisions for Tiktop Shop consumers